Effects of deformation temperature on edge crack characteristics and mechanical properties of as-cast aluminum alloy - Yongyue Liu; Peng Jiang; Xueping Ren; Xian Luo; Zelin Gu; Dsubianyu Fu (Functional Materials, 2018)
In this study, the rolling technique of aluminum alloy was investigated, and the effects of deformation temperature on the edge cracks and mechanical properties of aluminum alloy were studied through a hot compression experiment on high magnesium aluminum alloy. Based on the test, DEFORM-3D software was introduced to optimize the selection of the influence conditions of the experiment. The research results suggested that the crack length of the as-cast aluminum alloy samples decreased with the increase of temperature when the deformation temperature was between 300 °C and 450 °C; the tensile strength and elongation after fracture increased with the increase of temperature when the deformation temperature was between 300 °C and 500 °C. Therefore it is concluded that the cracks of high magnesium aluminum alloy can be reduced through controlling deformation temperature, which provides an idea for the optimization of aluminium alloy.